Periadolescent Exposure to the NMDA Receptor Antagonist MK-801 Impairs the Functional Maturation of Local GABAergic Circuits in the Adult Prefrontal Cortex - Thomases, Daniel R. (Society for Neuroscience, 2013)
A developmental disruption of prefrontal cortical inhibitory circuits is thought to contribute to the adolescent onset of cognitive deficits observed in schizophrenia. However, the developmental mechanisms underlying such a disruption remain elusive. The goal of this study is to examine how repeated exposure to the NMDA receptor antagonist dizocilpine maleate (MK-801) during periadolescence [from postnatal day 35 (P35) to P40] impacts the normative development of local prefrontal network response in rats. In vivo electrophysiological analyses revealed that MK-801 administration during periadolescence elicits an enduring disinhibited prefrontal local field potential (LFP) response to ventral hippocampal stimulation at 20 Hz (beta) and 40 Hz (gamma) in adulthood (P65–P85). Such a disinhibition was not observed when MK-801 was given during adulthood, indicating that the periadolescent transition is indeed a sensitive period for the functional maturation of prefrontal inhibitory control. Accordingly, the pattern of prefrontal LFP disinhibition induced by periadolescent MK-801 treatment resembles that observed in the normal P30–P40 prefrontal cortex (PFC). Additional pharmacological manipulations revealed that these developmentally immature prefrontal responses can be mimicked by single microinfusion of the GABA(A) receptor antagonist picrotoxin into the normal adult PFC. Importantly, acute administration of the GABA(A)-positive allosteric modulator Indiplon into the PFC reversed the prefrontal disinhibitory state induced by periadolescent MK-801 to normal levels. Together, these results indicate a critical role of NMDA receptors in regulating the periadolescent maturation of GABAergic networks in the PFC and that pharmacologically induced augmentation of local GABA(A)-receptor-mediated transmission is sufficient to overcome the disinhibitory prefrontal state associated with the periadolescent MK-801 exposure.